(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the fact that social norms are an integral part of the management of society, that social norms are a set of rules that harmonize the behavior of an individual or a social group with a certain social environment, the nature of serious changes and trends in the system of social norms during the globalization period, and the impact on character deviation the role of modern factor research principles. In the process of analyzing this article, special attention was paid to the harmony of social and moral relations in the growing up of the young generation. In the course of the research, the role of behavioral prevention and psychological factors in working with minors was explained.